Pemodelan Pemilihan Moda Transportasi Udara Dan Darat Rute Lhokseumawe-Medan - Syibral Malasyi; Suci Desna; Herman Fithra; Hafli, Teuku Mudi; David Sarana; Mukhlis (Universitas Iskandar Muda, 2025)
The choice of transportation mode is influenced by various travel characteristics and individuals’ socio-economic factors. This study employed an observational method followed by multiple linear regression analysis to identify the factors affecting mode choice, as well as a binary logit model to estimate the probability of selecting each mode. Data were collected through a questionnaire survey of 296 respondents. The results indicate that land transportation modes (public buses and minibuses) were more commonly chosen by female respondents, aged ≤30 years, with a high school education, who were students, had a monthly income of ≤Rp3,000,000, travel costs of ≤Rp300,000, and travel times of ≥3 hours. In contrast, air transportation tended to be chosen by male respondents, aged >30 years, holding a bachelor's degree, employed as civil servants, and earning more than Rp3,000,000, with the main reason being comfort despite the higher travel cost (>Rp300,000). The regression analysis showed that gender, education level, monthly income, travel cost, and travel time significantly influenced transportation mode choice. The binary logit model estimated a 60% probability for choosing air transportation and 40% for land transportation. These findings provide valuable input for transportation planners in formulating policies to improve accessibility and the quality of transportation services.